Strain Improves Risk Prediction Beyond Ejection Fraction in Chronic Systolic Heart Failure. Issue 1 (13th January 2014) - Zhang, Kathleen W.; French, Benjamin; May Khan, Abigail; Plappert, Ted; Fang, James C.; Sweitzer, Nancy K.; Borlaug, Barry A.; Chirinos, Julio A.; St. John Sutton, Martin; Cappola, Thomas P.; Ky, Bonnie
Abstract : Background: The utility of longitudinal, circumferential, and radial strain and strain rate in determining prognosis in chronic heart failure is not well established. Methods and Results: In 416 patients with chronic systolic heart failure, we performed speckle‐tracking analyses of left ventricular longitudinal, circumferential, and radial strain and strain rate on archived echocardiography images (30 frames per second). Cox regression models were used to determine the associations between strain and strain rate and risk of all‐cause mortality, cardiac transplantation, and ventricular‐assist device placement. The area under the time‐dependent ROC curve (AUC) was also calculated at 1 year and 5 years. Over a maximum follow‐up of 8.9 years, there were 138 events (33.2%). In unadjusted models, all strain and strain rate parameters were associated with adverse outcomes ( P <0.001). In multivariable models, all parameters with the exception of radial strain rate ( P =0.11) remained independently associated, with patients in the lowest tertile of strain or strain rate parameter having a ≈2‐fold increased risk of adverse outcomes compared with the reference group ( P <0.05). Addition of strain to ejection fraction (EF) led to a significantly improved AUC at 1 year (0.697 versus 0.633, P =0.032) and 5 years (0.700 versus 0.638, P =0.001). In contrast, strain rate did not provide incremental prognostic value to EF alone. Conclusions: Longitudinal and circumferential strain and strain rate, and radial strain are associated with chronic heart failure prognosis. Strain provides incremental value to EF in the prediction of adverse outcomes, and with additional study may be a clinically relevant prognostic tool.